The effect of graphite flakes (GFs) and hybrid graphene nanoplatelets (GNPs) particles to the mechanical properties of epoxy composites - Nurhazwani, Abu Bakar; Mohd Arif, Zulkarnain; Wan Anuar, Wan Hassan; Ramli, Junid; Jeefferie, Abd Razak; Mohd Muzafar, Ismail (Universiti Malaysia Pahang, 2020)
This paper reports the effects of epoxy when reinforced with graphite flakes (GFs) and was compared to epoxy reinforced by hybrid reinforcements consisted of graphite flakes (GFs) and grapheme nanoplatelets (GNPs). DGEBA, the type of epoxy which has been used in this work was added with 2, 4 and 6 wt.% of reinforcement respectively, relative to the total weight of the mixture. Nanocomposites was prepared using mechanical stirrer, stirred at 2000 rpm for 30 minutes followed by curing in the oven. The flexural testing shows that the epoxy/GFs composites has higher modulus compared to epoxy/GFs+GNPs. At 4wt.% filler loading, epoxy containing GFs exhibited 132% enhancement of modulus relative to neat epoxy. At the same filler amount, epoxy containing GFs+GNPs demonstrated slightly lower magnitude than system containing GFs with only 27% increase in modulus. However, addition of higher filler loading to the epoxy resin caused the modulus to decrease in magnitude speculated due to agglomeration of particles within the host matrix. The Charpy impact testing indicated similar pattern with epoxy/GFs system exhibited higher capability in absorbing energy than epoxy/GFs+GNPs where the peak was obtained at 4wt.% filler loading. At this amount of filler, 18.36 J/m increase in energy absorbed was recorded for epoxy/GFs compared to 2.13 J/m increased for epoxy/GFs+GNPs composite. Higher amount of filler loading added into epoxy only deteriorate the impact energy absorb by the sample. The hardness test show similar pattern of result with epoxy/GFs shows higher resistance in scratching compared to epoxy/GFs+GNPs.